Special diagnostic assessment form (Part 2) - Md Mustafa, Md Muziman Syah; Ahmad, Norsham (2020)
This special diagnostic assessment form (Part 1) is developed as a tool to evaluate Optometry students' performance in conducting special diagnostic tests and interpreting the result of the tests in Primary Optometry Clinic I. It includes visual field, binocular indirect ophthalmoscopy, Functional Actuity Contrast Test (FACT), Pelli-Robson, gonioscopy, pachymetry, A-scan and condensing lens test/procedures